2011
DOI: 10.1007/s00266-011-9725-9
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Autologous Scaffold for Diced-cartilage Grafts in Dorsal Augmentation Rhinoplasty

Abstract: The use of ATG to stabilize diced-cartilage grafts is a safe, reliable technique for dorsal nasal augmentation. The platelet gel provides growth factors while the fibrin glue creates a scaffold that allows stabilization and diffusion of nutrients to the cartilage graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 48 publications
1
55
0
2
Order By: Relevance
“…More recently, a technique based on placing finely diced cartilage over the dorsum and bonding the cartilage in situ with autologous platelet gel has been reported. 2 A different approach was chosen by fashioning a diced or slivered cartilage graft on the side table, using commercial tissue glue. 3,4 This technique allows for a wide variety of configurations and, given the ease with which the sides and ends of the graft can be tapered, lends itself in particular to segmental augmentation of the dorsum.…”
Section: Surgical Techniquementioning
confidence: 99%
“…More recently, a technique based on placing finely diced cartilage over the dorsum and bonding the cartilage in situ with autologous platelet gel has been reported. 2 A different approach was chosen by fashioning a diced or slivered cartilage graft on the side table, using commercial tissue glue. 3,4 This technique allows for a wide variety of configurations and, given the ease with which the sides and ends of the graft can be tapered, lends itself in particular to segmental augmentation of the dorsum.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Other advantages include the ready availability from the patient, lower rate of infections, and potential extrusion of synthetic graft. 6 The long-term outcome of Erol's "Turkish delight" technique 1 was disputed by Calvert et al 2 who concluded that Surgicel has a deleterious effect on the viability of diced cartilage. These points give heavy weighting to the use of fascia as a wrapper in dorsal augmentation.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The use of temporal fascia has the disadvantage of requiring a further incision, which is not necessary if using Surgicel or autologous tissue glue. 6 We aimed to introduce a modified single incision for harvesting both conchal cartilage graft and temporal fascia, with the objective of improving the aesthetic outcome of the procedure as well as reducing perioperative time. This technique is particularly useful in secondary rhinoplasty surgery, where septal cartilage may be in short supply.…”
mentioning
confidence: 99%
“…Bullocks et al used autologous tissue glue (obtained from platelet rich and platelet poor plasma)as a scaffold for the diced cartilage graft in 68 patients and found this method to be safe and reliable for augmentation. 10 Diced cartilage glue graft (Tisseel, a human thrombin and fibrinogen with bovine aprotinin as fibrinolysis inhibitor) has been tried by Tasman et al and a study of its morphologic longevity has been studied using ultrasound in a series of 28 patients and the results are encouraging in terms of reduced operating time and graft stability.…”
Section: Discussionmentioning
confidence: 99%